A Critical Analysis of Job Satisfaction and Employee Performance among High School Teachers in Odisha - Panda, Ranjan Kumar; Samantaray, Alaka; Panda, Sanjukta (Journal of Neonatal Surgery, 2025)
This study presents a critical analysis of the relationship between job satisfaction and employee performance among high school teachers in Odisha. By combining empirical data with theoretical reflection, it evaluates how satisfaction factors such as autonomy, recognition, and institutional support affect performance. Quantitative tools were used to assess satisfaction levels and their correlation with performance indicators. The study provides visual analysis, robust statistical interpretation, and actionable policy recommendations for state education authorities to reform school governance with a human-centered approach